Effects of SGLT-2 inhibitors on clinical and biological hyperandrogenism and menstruation irregularities in patients with polycystic ovary syndrome: A systematic review of randomized trials - Houcem Elomma Mrabet; Houda Ben Salem; Taieb Ach; Asma Ben Abdelkarim; Wafa Alaya (SAGE Open Medicine)
Introduction: Polycystic ovary syndrome is a common chronic condition characterized by insulin resistance and hyperandrogenism, leading to significant health risks and impaired quality of life. Sodium-glucose transporter type 2 inhibitors have shown promise in improving the metabolic profile of women with polycystic ovary syndrome. However, their impact on hormonal parameters and cycle disorders remains uncertain. Methods: This systematic review analyzed randomized clinical trials published up to 1 December 2023, comparing sodium-glucose transporter type 2 inhibitors to metformin, other antidiabetic agents, or placebo in women with polycystic ovary syndrome. The primary outcomes were changes in total testosterone, free androgen index, dehydroepiandrosterone sulfate, delta-4 androstenedione, and cycle disorders. Results: Five randomized studies were included, evaluating canagliflozin, dapagliflozin, licogliflozin, or empagliflozin against metformin, exenatide, or placebo, with a total of 214 participants. Improvements in total testosterone and dehydroepiandrosterone sulfatewere observed in some studies, but the effects were inconsistent across drugs and outcomes. Additionally, two studies reported beneficial effects on cycle disorders. Conclusions: Sodium-glucose transporter type 2 inhibitors appear to have a potential but variable impact on hormonal parameters in women with polycystic ovary syndrome. However, larger and longer-duration studies are needed to fully elucidate their long-term efficacy in addressing hyperandrogenism and improving overall outcomes in these patients.